Independent and interactive effects of eye rubbing and atopy on keratoconus - Yang, Kaili; Li, Dan; Xu, Liyan; Pang, Chenjiu; Zhao, Dongqing; Ren, Shengwei (Frontiers in Immunology, 2022)
Purpose: To evaluate the independent and interactive effects of eye rubbing and atopy on keratoconus (KC) in central China. Methods: A total of 330 KC patients and 330 controls were recruited in the case-control study. Eye rubbing and history of atopy were recorded through face-to-face interviews. The association between KC and eye rubbing, atopy, interactive effects of eye rubbing and atopy were analyzed by logistic regression, and the odds ratios (OR), relative excess risk due to interaction (RERI), attributable proportion (AP), synergy (S) index, and 95% confidence intervals (95% CI) were calculated. Results: A total of 228 patients (69.09%) had an eye rubbing history, and 53 (16.06%) had an atopy history in the KC group, which were both higher than that in the control group (p<0.001). Eye rubbing and atopy were positively associated with KC in multivariate analysis, with ORs (95% CIs) of 15.11 (10.02, 22.80) and 5.30 (2.59, 10.84), respectively. Compared to non-eye rubbing and non-atopy eyes, the risk for eye rubbing coexisted with atopy was 52.31 (12.25, 223.35). No significant associations were found between KC and multiplicative interaction (p=0.608). The RERI, AP, and S values were 32.89 (-43.35, 109.14), 0.63 (0.05, 1.21), and 2.79 (0.56, 13.96), respectively, with no significant association between additive interaction and KC. No significant associations were found between eye rubbing, atopy and the severity of KC (p>0.05). Conclusion: Eye rubbing and atopy were separately positively associated with KC, and there was a strong impact of coexistent eye rubbing and atopy on KC in China. Further multi-center and cohort study need to be conducted to explore the role of eye rubbing and atopy in the occurrence and development of KC.